Contemporary camareros: Santos sponsorship in the Philippines today - Tamayo, Jose Antonio Lorenzo L. (Animo Repository, 2020)
The use of religious images was already present in Filipino culture before the arrival of the Spaniards. With the coming of Christianity and the establishment of the Philippines as a Spanish colony, indigenous statues were replaced with Catholic images and icons, the santo. Records from the 17th to the 19th century show that missionaries relied on secular help in establishing a system of sponsorship for religious images. Those who sponsored santos were called camareros. This study aims to expand the work of Venida [1996, pp. 500-513] and Galang [2012, pp. 45-60], which focused on rural aristocracy and the traditional system of sponsorship for religious images established during the Spanish colonial period. Using anecdotes, personal interviews and a survey of camareros, the present study explores new systems of sponsorship for religious images in the twenty-first century, and describes the demographics, motivations, interactions, finances and santo collections of contemporary camareros. © 2020 National Folk Museum of Korea. All rights reserved.